Large-Coessential and Large-Coclosed Submodules - Abduljaleel , Amira A.; Yaseen, Sahira M. (Iraqi Journal of Science, 2021)
The goal of this research is to introduce the concepts of Large-coessential submodule and Large-coclosed submodule, for which some properties are also considered. Let M be an R-module and K, N are submodules of M such that , then K is said to be Large-coessential submodule, if . A submodule N of M is called Large-coclosed submodule, if K is Large-coessential submodule of N in M, for some submodule K of N, implies that .